Virtual Worlds : Heritage and Educational Challenge - Banek Zorica, Mihaela; Špiranec, Sonja; Pavlina, Krešimir (2007)
The authors give a brief overview of the development and current trends in the field of virtual worlds. The emphasis is put on one of the social network virtual worlds - Second life and its usage in educational environment and heritage preservation. Furthermore, the first phases of creating of the extended educational environment of the Department of Information Sciences, Faculty of Humanities and Social Sciences, University of Zagreb are shown.
Projekt MZOS
ENG